1992
DOI: 10.1037/0882-7974.7.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Age and forgetfulness: Perceivers' impressions of targets' capability.

Abstract: In a person perception paradigm, 72 young and 72 old adult Ss listened to tape recordings of a nonforgetful, moderately forgetful, or highly forgetful female target person being interviewed for a volunteer job. Ss then rated their opinion of the target's memory and how likely they would be to assign the target to easy and difficult tasks. Overall, Ss gave higher memory opinion ratings to old than to young targets. As expected, they were more likely to assign tasks to nonforgetful than to forgetful targets. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 14 publications
5
50
3
Order By: Relevance
“…During the interview the target either failed to remember various items of information (e.g., her social security number, the interviewer's name) or forgot nothing. Erber et al (1992) found that forgetfulness was clearly salient in perceivers' judgments about about the target's cognitive capability: Perceivers were less likely to assign tasks of varying difficulty to forgetful targets than to nonforgetful targets, thus confirming that memory is considered an important part of cognitive capability. However, contrary to the expected outcome that forgetful old targets would be judged more harshly, Erber et al (1992) found that perceivers were no less likely to assign tasks to forgetful old than to forgetful young targets.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…During the interview the target either failed to remember various items of information (e.g., her social security number, the interviewer's name) or forgot nothing. Erber et al (1992) found that forgetfulness was clearly salient in perceivers' judgments about about the target's cognitive capability: Perceivers were less likely to assign tasks of varying difficulty to forgetful targets than to nonforgetful targets, thus confirming that memory is considered an important part of cognitive capability. However, contrary to the expected outcome that forgetful old targets would be judged more harshly, Erber et al (1992) found that perceivers were no less likely to assign tasks to forgetful old than to forgetful young targets.…”
supporting
confidence: 50%
“…To test this hypothesis, Erber, Etheart, and Szuchman (1992) had perceivers listen to a tape recording of a young or old female target being interviewed for a school volunteer position. During the interview the target either failed to remember various items of information (e.g., her social security number, the interviewer's name) or forgot nothing.…”
mentioning
confidence: 99%
“…Age stereotypes can lead to organizational discrimination through confirmation biases. For example, when an older person fails to remember something, perceivers attribute the memory failure to intellectual incompetence, whereas the same failure by a younger adult is viewed as a temporary lapse due to inattention (Erber & Prager, 1999;Erber et al, 1992Erber et al, , 1993Erber et al, , 1996. Within organizations, older employees are viewed as less effective than younger employees in various job-related tasks (Avolio & Barrett, 1987;Rosen & Jerdee, 1976a,b;Singer, 1986).…”
Section: Warm But Incompetentmentioning
confidence: 99%
“…Fortunately, Caspi reports that inter-age contact serves to reduce stereotype-like attitudes [13]. Moreover, ensuring that individuals from two distinct groups interact has been shown to reduce stereotypical characteristic attributions [14]. Thus, if we incorporate inter-generational contact, on a one-to-one basis, into the study, we can reduce the stereotyping effect.…”
Section: Researcher Choicementioning
confidence: 99%